Gerakan Gen Z Menabung: Sosialisasi Perlindungan Hukum Terhadap Calon Nasabah Bank - Putri, Vindaniar; Gayatri Rejeki; Erwin Harinurdin; Adrian Zulkarnaen (Bhakti Persada Jurnal Aplikasi IPTEKS, 2024)
The number of cyber attacks on the banking industry in Indonesia is increasing every year, making people reluctant to save their money in banks. The Deposit Insurance Corporation (LPS) protects bank customer data and funds based on the applicable system and law. However, not many people know about the presence of LPS, so outreach and education about legal protection for bank customers is crucial before they have a bank account. High school students who are Generation Z are the right prospective bank customers to carry out outreach and education regarding legal protection for bank customers. Socialization and education were conducted at SMA Negeri 26 Jakarta, where 96 class XI students participated. The normalization gain method measures the effectiveness of socialization and education. The N-Gain test results were obtained at 77.39% using the pre-test and post-test values. These results prove that there has been an increase in students' knowledge about the legal protection of bank customer data and funds. Prospective and bank customers should not have to worry about their money stored in the bank because public funds will remain protected if a cyber attack occurs.